University and Academic Performance. Distortions and Anomalies of the Evaluative Culture in Chile - Santos-Herceg, J (UNIV CONCEPCION, BIBLIOTECA CENTRAL, 2020)
This text presents a critical approach to the evaluative culture currently present in most Chilean universities. This is done by analyzing the system of evaluation of the academic performance, particularly regarding research and publication. It is argued that there are distortions or anomalies caused by this system with regards to writing, the academic faculty and academic work which have had negative consequences on the development of university activity.